The Development of a Special Purpose Drink Based on Nut Raw Materials - Novikova, Zhanna Victorovna; Lavrinovich, Dmitry Sergeevich; Sergeeva, Sophie Mikhailovna; Maksimkin, Anton Alexeyevich (KnE Life Sciences, 2022)
To support health, efficiency and active longevity, a person needs to provide the body with the micronutrients necessary for metabolic processes. They must consume food in quantities that correspond to the physiological needs of the individual. Analyses of consumer demand have found that the human diet throughout life often includes dairy products.However, whole milk is often poorly tolerated by both the elderly and people with lactose intolerance (hypolactasia).This article examined the selection of alternative energy sources, focusing on the example of a drink that uses plant raw materials.Thus, the recipe of a new fermented drink based on nut raw materials was developed. The optimization of the hydromodule for the drink preparation from peanuts and hazelnuts, according to the content of the main food components and organoleptic quality indicators, was carried out. The chemical composition of the developed drink was established, a portion of which met 20% of the daily recommended value of vitamin B1, 16.8% of the daily value of niacin, and 15% and 19% of the daily value of iron and magnesium, respectively. The possibility of producing a fermented drink with nut raw materials as a complete replacement of cow’s milk was therefore shown to be justified. Keywords: specialized food, probiotic, vegetable raw materials, fermented drink, nuts